Simple mathematic for preschool using augmented reality - Tuan Mohamd Shafiq, Tuan Mohd Zahid (2019)
Simple Mathematic is a tool that is developed for preschool students to help them in learning mathematic subject in more interesting way using augmented reality technology. This tool also helps teachers to teach the students to become more understandable by getting the students’ interest and participation. Augmented Reality (AR) is a 3D virtual objects that are integrated into 3D real environment in real time. AR technology can help the students to improve their learning faster in a more fun environment. This project is conducted based on ADDIE model that include the process of analysis, design, development and evaluation. Each process is evaluated using the formative evaluation. At the end of the project a summative evaluation on the functions and interactivity of the system to validate the performance of the learning tool.